Evaluasi Formatif Penerapan Model E-Pembelajaran Program Pembatik Level 4 - Abduh, Moch.; Syarifuddin, Saleh; Isaeni, Nita (Jurnal Didaktika Pendidikan Dasar, 2025)
The role of formative evaluation in implementing e-learning as a learning tool in a teacher competency improvement program called Technology and Communication Based Learning (PembaTIK) is crucial. This study aims to determine the success of the implementation of the implementation of the training evaluation model 4. This study was conducted using a quantitative descriptive method, which was collected through an online survey questionnaire. The subjects of this study consisted of 498 respondents (48.8% of the 1,020 participant population) spread across 34 provinces at various levels of education units. The results of the study showed that: (1) at the reaction aspect, 95.9% of respondents stated a high level of satisfaction of Level 4 PembaTIK participants with the preparation of facilities and infrastructure; (2) at the learning aspect, 96.8% of respondents stated a high level of satisfaction with the implementation of the learning process followed and the support received during the training; and (3) At the behavioral aspect, 96.7% of respondents felt that there was a change in a positive/good direction in the attitudes and competencies of participants after participating in the learning process. So, it is concluded that there is an increase of competence in Technology and Communication Based Learning Level 4 through the application of e-learning.